2022
DOI: 10.1007/s11277-022-09969-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Coverage Optimization for 5G Ultra-dense Cellular Networks Based on Their User Densities

Abstract: This paper has proposed a user-density-based coverage optimization technique for ultradense cellular networks. Antenna tilting is a promising coverage optimization technique to be used in 5G networks that significantly improve the signal to interference plus noise ratio (SINR) by choosing the appropriate angle of tilt. In this paper, the cellular coverage has been optimized for scattered user densities/user-hotspots using an adaptive antenna tilting mechanism that steers the beams towards the temporal hot spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This allows us to quantify further outage reductions possible by optimally reassigning UEs across available cells. While several initial values are possible for Ã, we found that the RSRP-based assignment 10 for the considered network configuration γ( * ) worked sufficiently well in our scenario. By definition, the optimization in ( 13) requires the loadaware objective.…”
Section: A Gd-based Optimal Cell Assignmentmentioning
confidence: 63%
See 3 more Smart Citations
“…This allows us to quantify further outage reductions possible by optimally reassigning UEs across available cells. While several initial values are possible for Ã, we found that the RSRP-based assignment 10 for the considered network configuration γ( * ) worked sufficiently well in our scenario. By definition, the optimization in ( 13) requires the loadaware objective.…”
Section: A Gd-based Optimal Cell Assignmentmentioning
confidence: 63%
“…Typically, CCO centers around antenna parameters that can be controlled remotely, hence offering the possibility to retune the network configuration after deployment [1]. Specifically the optimal setting of the transmit power and the antenna downtilt is of interest [2], [3], [5], [10]- [21]. Overall, we can distinguish two strategies, either approaching the topic from a model-based or a model-free perspective.…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations